2012
DOI: 10.1039/c1cp22863c
|View full text |Cite
|
Sign up to set email alerts
|

On the interaction of Mg with the (111) and (110) surfaces of ceria

Abstract: Access to the full text of the published version may require a subscription. Please note that, in the typefaces we use, an italic vee looks like this: n, and a Greek nu looks like this: n. RightsWe will publish articles on the web as soon as possible after receiving your corrections; no late corrections will be made.Please return your final corrections, where possible within 48 hours of receipt, by e-mail to: pccp@rsc.org.Reprints-Electronic (PDF) reprints will be provided free of charge to the corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 75 publications
3
9
0
Order By: Relevance
“…As references, the spectra of a Pt foil, CeO 2 , as-prepared PtO x /CeO 2 , and Pt NPs/CeO 2 reduced in H 2 were also collected (Figure c). For Pt foil, the valence electronic structure is dominated by a broad partially occupied 5d-band in the region of −1.0 to 8.0 eV. , For CeO 2 , the valence band structure is dominant in the range of 2.0 to 8.0 eV, and the broad feature seen here is due to hybridized O 2p states. The valence band spectra of all the various Pt/CeO 2 samples are similar to that of CeO 2 , which is expected because of its dominant mass fraction in all of the latter samples. In Figure (c), the vertical line shows the positions of the maxima of XPS spectra for CeO 2 standard and various samples.…”
Section: Results and Discussionsupporting
confidence: 55%
“…As references, the spectra of a Pt foil, CeO 2 , as-prepared PtO x /CeO 2 , and Pt NPs/CeO 2 reduced in H 2 were also collected (Figure c). For Pt foil, the valence electronic structure is dominated by a broad partially occupied 5d-band in the region of −1.0 to 8.0 eV. , For CeO 2 , the valence band structure is dominant in the range of 2.0 to 8.0 eV, and the broad feature seen here is due to hybridized O 2p states. The valence band spectra of all the various Pt/CeO 2 samples are similar to that of CeO 2 , which is expected because of its dominant mass fraction in all of the latter samples. In Figure (c), the vertical line shows the positions of the maxima of XPS spectra for CeO 2 standard and various samples.…”
Section: Results and Discussionsupporting
confidence: 55%
“…It has been reported that a perfect stoichiometry of the CeO 2 contains a small concentration of oxygen vacancies. 61 It is expected that the addition of Al 2 O 3 to the Ce-Sm mixed oxide enhances its structural stability through Ce-O-Al interactions at the boundary of the Ce-Sm and Al 2 O 3 , and results in a small number of oxygen vacancies and low soot oxidation performance. A clear explanation can be found from density functional theory analysis of doped CeO 2 materials, which is under further investigation.…”
Section: Soot Oxidation Activity Studiesmentioning
confidence: 99%
“…In spite of numerous efforts undertaken so far,c omprehensiveu nderstandingo ff undamental changes in the electronic structureo ft he doped semiconductors is still not sufficientf or the rational designo ft heir atomicc omposition. It is necessary to formulate at heoretical procedure to predict prudently the electronic structure and the charge redistributioni np hotocatalysts.Anumbero fs imulations performed so far deal mainly with doped and codoped photocatalytic bulk materials, [52][53][54][55][57][58][59][60][61][62][63][64] and their low-index surfaces, [65][66][67] as well as 0D and 1D nanostructures. [68,69] There are two criticali ssues that are important for photocatalysis,b ut not yet well treated in conventional density functional theory,a sw ella so ther first-principles packages:1 )t he lack of resources,e ssential for simulations of the strong polarization on the charged electrode surfaces in aqueous electrolyte;a nd 2) the inaccuracyo f existing DFT functionals for ap ropera lignment of the H + /H 2 and H 2 O/O 2 potentials with the edges of the band gap or the induced dopant levels.…”
Section: Theoreticalsimulationsmentioning
confidence: 99%
“…[64] Using the PAWm ethodf or DFTc alculations,N olan found that small iron-oxide clusters can be stable at the TiO 2 surface,a nd their presence squeezes the band gap towards the frequencyr ange of visible light arising from the presence of iron-oxide states lying above the valence band of titania. [65] PW DFT calculations,i nc ombination with ultraviolet photoelectrons pectroscopy,h ave been used to study the origin of the band-gap states of ar utilestructured TiO 2 (110)s lab induced by surface ÀOH groups. [66] C-, N-and S-doped (TiO 2 ) n nanoclustersw ere studied by Shevlin and Woodley using both standard and time-dependent DFT calculations.…”
Section: Theoreticalsimulationsmentioning
confidence: 99%
See 1 more Smart Citation